DAMPAK TANAMAN TUMPANGSARI JERNANG TERHADAP PENDAPATAN PETANI KOPI DI KABUPATEN ACEH TENGAH - Bagus Apreza Tarman; Eddy Gunawan (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
AbstractThis study aims to analyze the income of coffee farmers before and after using dragon blood intercropping in Central Aceh, farmers who use coffee plantations switch to using dragon blood intercropping and coffee farming, can they experience an increase in income changes after land is used by planting two crops at once. The data used in this study are primary data obtained from observation and direct interviews. The total sample in this study were 31 household heads who after using coffee and intercropping dragon blood plants. From the results of this study, it is known that farmers who only plant coffee plants produce an average income of Rp120,822,580 a years and coffee farmers who use dragon blood plants experience an increase in average income of Rp260,139,516 a years. Coffee farmers who use coffee and intercropping dragon blood have more income than just planting coffee so that coffee and intercropping of dragon's blood are suitable for further development.Keywords: Intercropping, dragon blood Plants, Coffee Plants and dragon blood.